2021
DOI: 10.1186/s13020-021-00539-7
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine for adjuvant treatment of breast cancer: Taohong Siwu Decoction

Abstract: The high incidence of breast cancer is the greastest threat to women’ health all over the world. Among them, HER-2 positive breast cancer has the characteristics of high malignancy, easy recurrence and metastasis, and poor prognosis. Traditional Chinese medicine (TCM) has a rich theoretical basis and clinical application for breast cancer. TCM believes that blood stasis syndrome is one of the important pathogenesis of breast formation and development. Taohong Siwu Decoction (TSHWD) is based on the “First Presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 90 publications
(95 reference statements)
1
29
0
Order By: Relevance
“…The basis of the occurrence of malignant tumors is the weakness of vital qi, which is manifested in the low immune function. In TCM, the method of “Fuzheng cultivation” is adopted, which is to improve the immune function of the body by tonifying the innate kidney essence and the acquired spleen and stomach [ 19 ]. In the process of disease progression, patients often have deficiency syndromes such as spleen and stomach weakness, deficiency of qi and blood, depletion of yang qi, kidney failure, and deficiency of essence.…”
Section: Discussionmentioning
confidence: 99%
“…The basis of the occurrence of malignant tumors is the weakness of vital qi, which is manifested in the low immune function. In TCM, the method of “Fuzheng cultivation” is adopted, which is to improve the immune function of the body by tonifying the innate kidney essence and the acquired spleen and stomach [ 19 ]. In the process of disease progression, patients often have deficiency syndromes such as spleen and stomach weakness, deficiency of qi and blood, depletion of yang qi, kidney failure, and deficiency of essence.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine exhibits various unique properties like varied active substances, multiple key targets, and low toxicity [39]. More importantly, it has superior antitumor properties and can be used to treat different tumors, such as esophageal cancer, liver cancer, pancreatic cancer, and breast cancer [40][41][42][43]. The present study identified the key active ingredients and possible detailed molecular mechanisms of Dahuang against hepatoma through network pharmacology, molecular docking, and survival analysis.…”
Section: Discussionmentioning
confidence: 93%
“…QD-BS causes poor blood circulation in tumors, which is similar to the hypercoagulable state of tumor patients found in modern medicine. The formation of tumor thrombi is closely related to abnormal coagulation during tumor progression ( 22 ). Due to the characteristics of promoting blood circulation and improving the hypoxic microenvironment, a variety of Chinese herb and formulas for SQ-ABC have become vital adjuvant treatments in treatment of tumor, such as HMMCR, Huayu pill ( 23 , 24 ), Taohong Siwu Decoction ( 25 ), and Qizhu decoction ( 26 ).…”
Section: Discussionmentioning
confidence: 99%